Mountain men - Santella, Andrew (New York Children's Press, 2003)
A description of the mountain men, nineteenth-century explorers and fur traders who helped open up the West to United States settlement
American Corner
Includes bibliographical references (p. 46) and index
11
Keywords: Explorers -- West (U.S.) -- History -- 19th century -- Juvenile literature; Frontier and pioneer life -- West (U.S.) -- Juvenile literature; Frontier and pioneer life; Fur traders -- West (U.S.) -- History -- 19th century -- Juvenile literature; Pioneers -- West (U.S.) -- History -- 19th century -- Juvenile literature; Trappers -- West (U.S.) -- History -- 19th century -- Juvenile literature; West (U.S.) -- Biography -- Juvenile literature; West (U.S.) -- Discovery and exploration -- Juvenile literature; West (U.S.) -- History -- To 1848 -- Juvenile literature; West (U.S.) -- History -- To 1848